Problems of socio-geographical assessment of the tourist attractiveness of the region - Kolotukha, Oleksandr; Sokolovskiy, Viktor; Shchoholieva, Inna (Journal of Education, Health and Sport, 2017)
The article deals with the problems of the study of tourist attractiveness, identifies the main differences of the conceptual apparatus used in tourist studies of the regions, systematizes the criteria for evaluating the tourist attractiveness of the region, analyzes the existing methods and determines the factors of tourist attractiveness, determines the main stages of determining the rating of the tourist rating.